Rehabilitation for post-stroke cognitive impairment: an overview of recommendations arising from systematic reviews of current evidence. (February 2015) - Gillespie, David C; Bowen, Audrey; Chung, Charlie S; Cockburn, Janet; Knapp, Peter; Pollock, Alex
Background: Although cognitive impairments are common following stroke, there is considerable uncertainty about the types of interventions that can reduce activity restrictions and improve quality of life. Indeed, a recent project to identify priorities for research into life after stroke determined that the top priority for patients, carers and health professionals was how to improve cognitive impairments. Objective: To provide an overview of the evidence for the effectiveness of cognitive rehabilitation for patients with stroke and to determine the main gaps in the current evidence base. Methods: Evidence was synthesised for the six Cochrane reviews relating to rehabilitation for post-stroke cognitive impairment and any subsequently published randomized controlled trials to February 2012. Results: Data arising from 44 trials involving over 1500 patients was identified. Though there was support for the effectiveness of cognitive rehabilitation for some cognitive impairments, significant gaps were found in the current evidence base. All of the Cochrane reviews identified major limitations within the evidence they identified. Conclusions: There is currently insufficient research evidence, or evidence of insufficient quality, to support clear recommendations for clinical practice. Recommendations are made as to the research required to strengthen the evidence base, and so facilitate the delivery of effective interventions to individuals with cognitive impairment after stroke.